ANALISIS PERENCANAAN PAJAK UNTUK PPh PASAL 21 - Maksalmina Maksalmina (University Muhammadiyah Aceh, 2021)
This study aims to determine how the impact of the application of the Gross Method, Net Method, and Gross Up Method on the calculation of Income Tax Article 21 and which methods can be used as an alternative to tax efficiency. The research method used is comparative descriptive with quantitative measurements with primary data collection techniques, namely in the form of subject data from illustrations and documentary data in the form of a list of employee salaries in 202X from PT.X. The results showed that by using the Gross Method on the application of salary data in202X resulted in reduced employee income. The calculation using the Net Method resulted in the company's net profit increasing due to positive fiscal correction. Meanwhile, by using the Gross Up Method, the company provides tax allowances inthe same amount as the Income Tax Article 21 owed, in addition to the application of the Gross Up Method, the salary costs increase along with the decrease in the company's net income which will automatically reduce the burden of corporate income tax. From the results of these studies, it can be concluded that tax planning for PPh Article 21 with the Gross Up Method will provide benefits not only for the company but also for employees